Experimental realization of tunable finite square optical arrays. (September 2022) - Liu, Dadong; Gao, Binjie; Wang, Fujin; Wen, Jisen; Wang, Li-Gang
Highlights: Arbitrary order alternated optical vortex (OV) lattices with positive and negative topological charges, which are named as the n th-order alternated OV lattices (NAOVLs), are proposed theoretically and realized experimentally. The propagation properties of NAOVLs are explored both theoretically and experimentally in a focusing system or at far-field Fraunhofer region. Such NAOVLs can generate finite square optical arrays with interesting patterns or defects, and the phase dislocation lines contained in square optical arrays are confirmed by interference experiments. Abstract: Recently optical lattices containing optical vortices (OVs), which carry phase singularities and possess exotic optical properties, have attracted increasing attention due to their potential applications in optical trapping or light-matter interaction systems. Here, we propose a kind of arbitrary order alternated OV lattices with positive and negative topological charges ± n, which are named as the n th-order alternated OV lattices (NAOVLs), and we experimentally demonstrate their propagation properties. We find that such NAOVLs can generate finite square optical arrays with interesting patterns or defects near the focal plane or far-field Fraunhofer region. We further find a general law (although with some exceptions) about the number N of bright spots in finite optical arrays as the value n increases. The interference experiments confirm optical properties of such finite arrays close to the focal plane. Our results may have potential applications in particle trapping and experimental realizations of novel optical arrays for the interaction between special optical lattices and atoms (or molecules, ions, micro- or nano-particles).